Dialog antar Tokoh dalam Pertunjukkan Calon Arang - Suastika, I Made; Puspawati, Luh Putu (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
Calon Arang was originally in the form of literary works in various genres, such as prose, kidung, geguritan, speech (tatwa) and later appeared in the Kakawin Calon Arang and the novel of Calon Arang in Balinese. In the context of the art and culture of Calon Arang, it has been used for the theme of the Bali Arts Festival and the context of art was used in the play of Calon Arang. This is where a broad understanding of the story (text) of Calon Arang is found in several episodes such as Katundung Ratna Mangali, Madusang-dusangan, the Patih Madri episode, and the war between Mpu Baradah and Calon Arang which ends with the two characters being the embodiment of Rangda and Barong. In the Calon Arang performance, whether it's arja, prembon, or dance drama, there are differences in the dialogue language, such as the Calon Arang character and the character from the upper class using Old Javanese language. Meanwhile, the parekan figures such as Kartala (punakawan) are using Balinese language. The complete study of the dialogue in Old Javanese and Balinese language between the characters in the performing arts will be presented in this paper